Cytotoxicity assessment of polyhydroxybutyrate/chitosan/nano- bioglass nanofiber scaffolds by stem cells from human exfoliated deciduous teeth stem cells from dental pulp of exfoliated deciduous tooth - Batool Hashemi-Beni; Maryam Khoroushi; Mohammad Reza Foroughi; Saeed Karbasi; Abbas Ali Khademi (Wolters Kluwer Medknow Publications, 2018)
Background: The aim of this study was to compare the cytotoxicity and the biocompatibility of three different nanofibers scaffolds after seeding of stem cells harvested from human deciduous dental pulp. Given the importance of scaffold and its features in tissue engineering, this study demonstrated the construction of polyhydroxybutyrate (PHB)/chitosan/nano-bioglass (nBG) nanocomposite scaffold using electrospinning method. Materials and Methods: This experimental study was conducted on normal exfoliated deciduous incisors obtained from 6-year-old to 11-year-old healthy children. The dental pulp was extracted from primary incisor teeth which are falling aseptically. After digesting the tissue with 4 mg/ml of type I collagenase, the cells were cultured in medium solution. Identification of stem cells from human exfoliated deciduous teeth was performed by flowcytometry using CD19, CD14, CD146, and CD90 markers. Then, 1 × 104 stem cells were seeded on the scaffold with a diameter of 10 mm × 0.3 mm. Cell viability was evaluated on days 3, 5, and 7 through methyl thiazol tetrazolium techniques (P < 0.05) on different groups that they are groups included (1) PHB scaffold (G1), (2) PHB/chitosan scaffold (G2), (3) the optimal PHB/chitosan/nBG scaffold (G3), (4) mineral trioxide aggregate (MTA), and (5) the G3 + MTA scaffold (G3 + MTA). Data were analyzed with two-way ANOVA at significance level of P < 0.05. Results: The results indicated that the PHB/chitosan/nBG scaffold and PHB/chitosan/nBG scaffold + MTA groups showed significant difference compared with the PHB/chitosan scaffold and PHB scaffold groups on the 7th day (P < 0.05). Conclusion: Thus, it can be concluded that the scaffold with nBG nanoparticles is more biocompatible than the other scaffolds and can be considered as a suitable scaffold for growth and proliferation of stem cells.